Reserve Accumulation and International Monetary Stability. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
Since its last report to the IMFC in October 2009, the IEO has completed its evaluation report on IMF Interactions with Member Countries and finalized issues papers for evaluations on the IMF Performance in the Run-up to the Current Financial and Economic Crisis and Research at the IMF: Relevance and Utilization. On February 1, Moises Schwartz assumed his duties as the third Director of the IEO.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet